2019
DOI: 10.3390/catal9060550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Loading in Unpromoted and Promoted CoMo/Al2O3–TiO2 Catalysts for the Hydrodeoxygenation of Phenol

Abstract: This paper reports the effects of changes in the supported active phase concentration over titania containing mixed oxides catalysts for hydrodeoxygenation (HDO). Mo and CoMo supported on sol–gel Al2O3–TiO2 (Al/Ti = 2) were synthetized and tested for the HDO of phenol in a batch reactor at 5.5 MPa, 593 K, and 100 ppm S. Characterization results showed that the increase in Mo loading led to an increase in the amount of oxide Mo species with octahedral coordination (MoOh), which produced more active sites and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 72 publications
(134 reference statements)
6
12
1
Order By: Relevance
“…This change is much larger than that observed in the bimetallic 8CoO–13.5MoO x catalyst (Figure ), where only 15.8% of Co atoms are reduced. This result confirms that, without Mo, Co species are more reducible, that is, Co 3 O 4 or CoO species (in the monometallic 10CoO catalyst) are more likely to be reduced to metallic Co particles than the Co embedded in the CoMoO 4 structures, as also reported by others. As established, metallic Co, , together with other late transition metals (Ni, , Pt, ,, Pd, Ru, Rh , ), is extremely reactive for alkane reforming reactions rather than the oxidative dehydrogenation reaction. The reduced 10CoO sample displayed much higher turnovers, >20 times higher than those of CoO–MoO x series, but these C 2 H 6 turnovers led exclusively to reforming products (CO and H 2 ) without producing any ethylene.…”
Section: Resultssupporting
confidence: 87%
“…This change is much larger than that observed in the bimetallic 8CoO–13.5MoO x catalyst (Figure ), where only 15.8% of Co atoms are reduced. This result confirms that, without Mo, Co species are more reducible, that is, Co 3 O 4 or CoO species (in the monometallic 10CoO catalyst) are more likely to be reduced to metallic Co particles than the Co embedded in the CoMoO 4 structures, as also reported by others. As established, metallic Co, , together with other late transition metals (Ni, , Pt, ,, Pd, Ru, Rh , ), is extremely reactive for alkane reforming reactions rather than the oxidative dehydrogenation reaction. The reduced 10CoO sample displayed much higher turnovers, >20 times higher than those of CoO–MoO x series, but these C 2 H 6 turnovers led exclusively to reforming products (CO and H 2 ) without producing any ethylene.…”
Section: Resultssupporting
confidence: 87%
“…Others [ 61 ] have also found similar trends where CAT was produced by demethylation (OCH 3 bond rupture) during GUA HDO over alumina. In full agreement, Tavizón‐Pozos et al [ 62 ] reported production of so‐called ‘oxygenated intermediaries’, although no specific species were disclosed in that case. Interestingly, cyclohexene was also identified by those authors, with that being attributed to dehydration (from cyclohexanol [ 63,64 ] or cyclohexanone [ 64 ] ) on Brønsted acid sites provided by the equimolar alumina–titania carrier used.…”
Section: Resultsmentioning
confidence: 53%
“…We speculate that the promoter Ni exists as Ni x S y crystals after segregation from the active phase. For hydrotreating catalysts, the X-ray photoelectron spectroscopy (XPS) technique has been among the tools most often used to obtain chemical states information on the promoter atoms in hydrotreating catalysts [32][33][34][35]. Therefore, XPS was performed for the catalysts in order to verify our speculation.…”
Section: Catalyst Hds (%) Hdn (%)mentioning
confidence: 99%